2016
DOI: 10.1371/journal.pone.0154856
|View full text |Cite
|
Sign up to set email alerts
|

Case-Only Survival Analysis Reveals Unique Effects of Genotype, Sex, and Coronary Disease Severity on Survivorship

Abstract: Survival bias may unduly impact genetic association with complex diseases; gene-specific survival effects may further complicate such investigations. Coronary artery disease (CAD) is a complex phenotype for which little is understood about gene-specific survival effects; yet, such information can offer insight into refining genetic associations, improving replications, and can provide candidate genes for both mortality risk and improved survivorship in CAD. Building on our previous work, the purpose of this cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…Outside CNS, the highest expression level was observed for Lsamp 1b transcript in the heart, which is in line with considerable evidence suggesting that IgLONs, specifically Lsamp and Ntm , may have additional functions in the human cardiovascular system (Wang et al, 2008 ; Luukkonen et al, 2012 ; Cao et al, 2015 ; Dungan et al, 2016 ). However, data from knockout mouse models has demonstrated that deletion of either Lsamp, Ntm , or Opcml individually, or Opcml and Ntm together as a double heterozygote, does not result in apparent cardiac phenotype (Innos et al, 2011 ; Ye et al, 2014 ).…”
Section: Discussionsupporting
confidence: 76%
“…Outside CNS, the highest expression level was observed for Lsamp 1b transcript in the heart, which is in line with considerable evidence suggesting that IgLONs, specifically Lsamp and Ntm , may have additional functions in the human cardiovascular system (Wang et al, 2008 ; Luukkonen et al, 2012 ; Cao et al, 2015 ; Dungan et al, 2016 ). However, data from knockout mouse models has demonstrated that deletion of either Lsamp, Ntm , or Opcml individually, or Opcml and Ntm together as a double heterozygote, does not result in apparent cardiac phenotype (Innos et al, 2011 ; Ye et al, 2014 ).…”
Section: Discussionsupporting
confidence: 76%
“…However, with an increasing focus on the genetic context of subsequent CHD 5 , a more specific question has arisen about the impact of selection bias in studying those who have been selected on and have survived a potentially fatal index event. While some studies have examined the impact of selection bias on effect estimates in case-control studies 18,19 , to our knowledge this question has not been addressed for time to event analysis of longitudinal cohort studies exploring associations with recurrent or subsequent CHD events.…”
Section: Discussionmentioning
confidence: 99%
“…We included only self-reported White participants for two reasons: First, the frequency of self-reported Black/African American individuals with CAD in the extant GWAS datasets was insufficient for stratified analyses (n = 126 and 124 for the discovery and replication cohorts, respectively). Second, our goal is for the present GWA screen to be comparable to the findings of our prior work as we look to build genomic convergence for this phenotype, and the sample for our earlier candidate gene study of survivorship with CAD comprised White individuals (Dungan et al, 2016).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…We defined time to event as the number of days from study enrollment (time at coronary catheterization and blood collection) to death from any cause. Data from surviving individuals were censored on the date of the last follow-up, consistent with our "survivorship with CAD" phenotype (Dungan et al, 2016). For our analyses of SNPs, we assumed an additive genetic model based on preliminary data demonstrating additive genetic effects (Dungan et al, 2016).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation